Features of Metabolic Processes in Children Born by Caesarean Section in the Early Adaptation Period: the Role of Cerebral Ischemia - Т. S. Tumaeva; L. А. Balykova ("Paediatrician" Publishers LLC, 2015)
Background: The postnatal adaptation comprises alteration of metabolic processes of a newborn, the disturbance of which can lead to dysfunction, and later - to the development of diseases. Objective: Our aim was to study the bond of cerebral ischemia in full-term children born by Caesarean section with the course of metabolic processes in the early neonatal period. Methods: A retrospective comparative study was conducted. Children born by Caesarean section, who had cerebral ischemia (n =120) and who didn't have it, (n = 150) were examined. Complex examination included an assessment of a number of factors: clinical, biochemical blood tests, acidbase balance, concentration of some hormones. Results: In children after Caesarean section with cerebral ischemia in the early period of adaptation we noted disturbances of the acid-base balance (BE 0.3 ± 1.9 mmol/l; р = 0.038), blood oxygenation (SaO2 79.7 ± 2.8%; р = 0.001), frank lactataemia (4.3 ± 1.8 mmol/l; р = 0.002), signs of a catabolic orientation of metabolism (hypoproteinemia, increased protein metabolism products, frank primary loss of body weight). The considerable changes of activity of the blood enzymes, disturbance of glucose metabolism indicated the lack of energy-dependent processes. Due to this, the hyperbilirubinemia and a hormonal imbalance were more often formed. Conclusion: Cerebral ischemia in children born by Caesarean section is a reason for the development of a metabolic disadaptation. The detection of disturbances of metabolic processes in the early neonatal period is necessary for a timely start of the correctional therapy in order to prevent the development of diseases in more distant periods of a child's life.